Internal whistleblowing practices in enhancing good corporate integrity among employees at public listed companies / Natrah Abdullah - Abdullah, Natrah (2018)
Whistleblowing has been receiving increases attention and support in today critical economic condition as the practice of whistleblowing may be used in detecting and correcting wrongdoing in organizations. Malaysia is known as one of the most corrupt countries even though the government has always provided various initiatives to encourage the whistleblowing practices. Nevertheless, whistleblowing still not well exposed for Malaysian as the issue regarding whistleblowing not really being supported in this country. However, whistleblowing need to be openly exposed to the society because it will benefit organizations. Therefore, this study aims to examine the factors that may influence internal whistleblowing practices. This is because internal whistleblowing practices is perceived as a mechanism that can enhance accountability and honesty in organizations and create change by deterring and detecting wrongdoing which includes unethical acts, corporate fraud, mismanagement and corruption especially within the organizations. Thus, the specific objectives of the study are to identify the relationship between implementation of whistleblowing policy, legislative protection, communication channels and organizational may encourage the internal whistleblowing practices in enhancing good corporate integrity among employees. This study is based in Kuala Lumpur and focused on the lower, middle as well as upper level of employees in financial and banking sector which has been listed under Bursa Malaysia. This study shows that internal whistleblowing practices may enhance good corporate integrity in an organization.